The Role of Educators/Teachers and Students in the Process of Teaching and Learning Activities - Siregar, Nujuluddin; Gufron, Uup; Kartono, Kartono (STKIP PGRI Tulungagung, 2024)
Community Service Activities at SMK Cakra Nusantara Depok are as a means of social servicein the context of Community Service and the application of science and technology to delivermaterial on 'The Role of Educators/Teachers and Students in the Process of Teaching andLearning Activities' in addition to sharing teaching experiences according to with the field andbackground of the educators at the Foundation. What is our role as teachers so far in educatingand developing students' spiritual, emotional, intellectual, ethical intelligence in their lives, andhow educators apply learning theory while understanding their role, especially in the process oflearning foreign/English language activities at the educational foundation. How to apply learningtheory in various fields of school study is not easy, in addition to requiring professional abilityand responsiveness, of course, concern for learning itself is very important for each individualeducator. In this Millennial era, all circles are anesthetized by the rapid flow of informationtechnology, the era of the Industrial Revolution 4.0 or even 5.0 is accompanied by various fastpaced, instant and online life activities, so the responsibility of parents, especially teachers, iseven more difficult, namely preparing the next generation. The tough ones are ready to face anysituation, however that lies before them. One of the skills that they must possess and honecontinuously is the ability to master a foreign/English language which is a window for otherknowledge to be opened. Humans are born in the world not with an empty plate (the theory oftabula rasa). Because every human being has been equipped with what are called 'faculties of themind', one part of which is specially created for language acquisition (Noam Chomsky, UniversalLanguage, 1959).